IN SURKHANDARYA SOIL CLIMATE, ITBURUN NAMATAK (R. CANINA) TO DETERMINE CULTIVATION AND YIELD - Ermatov Dilshodbek son of Jora; Turakulov Alimardon Abdusalomovich (Web of Journals Publishing, 2024)
The study focuses on the cultivation and yield of Itburun Na’matak (Rosa canina), a wild rose species, in the specific soil and climate conditions of the Surkhandarya region. This research investigates the optimal growing conditions, soil requirements, and the plant’s adaptability to the region. The results provide insights into potential agricultural and economic benefits, suggesting that Surkhandarya’s soil and climate are conducive to successful cultivation, with a promising yield for both local and commercial use.
Keywords: Itburun Na’matak, Rosa canina, cultivation, Surkhandarya, yield, soil-climate conditions, wild rose, medicinal plant.